Potensi Senyawa Bioaktif Kulit Kayu Syzygium cumini Sebagai Agen Antikanker dan Antimikroba: Sebuah Tinjauan Pustaka - Syahfitri, Widya; Hasibuan, Febry Rahmadhani; Maelani, Imelda; Manulu, Adelia Irawan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2026)
The Jamblang bark of Syzygium cumini contains diverse bioactive secondary metabolites with notable anticancer and antimicrobial potential. This review summarizes recent studies on the active compounds of S. cumini bark and their underlying biological mechanisms. A literature review was conducted following PRISMA-based guidelines by searching databases including PubMed, ScienceDirect, and Google Scholar for articles published between 2010 and 2025. Studies were selected based on relevance to S. cumini bark, phytochemical composition, and anticancer or antimicrobial activity. The results indicate that S. cumini bark major constituents include flavonoids (quercetin, kaempferol, myricetin), phenolic acids (ellagic acid, gallic acid), tannins, and triterpenoids (friedelin, betulinic acid). These compounds exhibit anticancer activity by inducing apoptosis and inhibiting cancer cell proliferation through pathways such as NF-κB suppression (ellagic acid) and mitochondrial activation (betulinic acid). In antimicrobial studies, the n-hexane fraction of S. cumini bark extract effectively inhibits Salmonella typhi, likely via cell wall disruption by flavonoids and tannins. A summary of the active compounds and their biological activities is presented in tabular form. Overall, S. cumini bark demonstrates strong potential as a source of phytopharmaceutical candidates for anticancer and antibacterial development, highlighting the need for further compound isolation and pharmacological validation. Keywords: Anticancer, antimicrobial, Syzygium cumini, bark, bioactive compound